Efek Campuran Sedimen Embung Terhadap Karakteristik Bata Berbahan Dasar Pasir Batu Apung - Meilyna Angellyna; Mufti Amir Sultan; Nurmaiyasa Marsaoly (Jurnal Karajata Engineering, 2025)
The Sofifi Reservoir aims to store water to provide raw water and utilize groundwater for the needs of the Sofifi community. Sediment deposition in the reservoir is due to community activities around the reservoir location and erosion on the slopes around the reservoir. Sediment that enters the reservoir bag will cause a decrease in the performance of the reservoir. In order to utilize the reservoir sediment, research was conducted using the sediment as raw material for making bricks. The research was carried out in the laboratory by making bricks using pumice sand and Sofifi reservoir sediment as raw materials. Variations of test objects with the composition of reservoir sediment and pumice sand 0%:100%, 20%:80%, 40%:60%, 60%:40%, 80%:20% and 100%:0% of the aggregate volume. Testing of visible properties, suitability of size, volume weight and compressive strength of bricks. The test results show that the quality of the bricks produced at a composition of 1:4 with a reservoir sediment content of 0% to 40% produces bricks of quality 100. A sediment content of 60% to 100% with a composition of 1:4 produces bricks of quality 50.